Vida e pensamento: considerações sobre a Filosofia numa perspectiva genealógica - Monteiro, Átila Brandão (2021)
The present thesis invites a reflection on philosophy itself, trying to conceive it not as a universal doctrine, nor under the sign of theory or criticism, nor as a form of life, but as something that permeates all these forms and the they make it possible, namely, as a determined activity of thought, creative, mobilized by vital problems, by questions of meaning and value. In this sense, our goal is to think of philosophy as a “human” production, taking in a radical way what this can mean. Thus, we intend to argue that in thinking there are a series of elements that not only condition and determine philosophy, but also make it possible and necessary, providing its reason for being in the economy of human existence: organic and vital demands, unconscious and instinctive, but also conscious and linguistic, collective and regulatory - in short, demands for meaning and orientation. To develop this reflection, our fundamental reference is the Nietzschean genealogical criticism, since it provides an interpretive lens that highlights precisely the vital elements that are at stake in the production of thought. Therefore, the first part of this thesis (which comprises two chapters) is dedicated to the reconstruction of Nietzsche's genealogical criticism, especially with regard to what links it to our theme: historical deconstruction of essentialist thinking, emphasis on the discrepancy between the possibilities of thinking in relation to the essentialist pretensions of metaphysics and, finally, the convergence of these reflections in the thematization of the “interested” nature of human thought, as it is moved and conditioned by certain values that shape forms of life. The second part (which comprises the following three chapters) seeks, in turn, to develop the elements that arise from genealogical criticism towards a productive notion of thought and, consequently, of philosophy. Thus, our effort in this part is to conceive thought from another perspective, emphasizing its possibilities and potentialities, its richness and peculiarity as the productive capacity of a speaking living being. In it we make a general outline in which perspectives around the human are articulated, thinking their condition in a radical way: as a living, temporal, organic, gregarious, linguistic, desiring and creative being, in a dialogue with Bergson, Maturana and Freud. This discussion aims to glimpse the possibilities and potencies of thought when detached from hostile demands to life and aligned with valuing the body, affections and immanence.